Handbook of visual communication theory, methods, and media - Josephson, Sheree; Kelly, James D. 1957-; Smith, Ken 1947 August 14-
"This Handbook of Visual Communication explores the key theoretical areas and research methods of visual communication. With chapters contributed by many of the best-known and respected scholars in visual communication, this volume brings together significant and influential work in the discipline"--Provided by publisher.
SMC Sanchez (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Visual communication; Visual communication -- Methodology